Vasoconstriction Seen in Coronary Bypass Grafts During Handgrip in Humans - Momen, Afsana (2006)
In animal studies, sympathetically mediated coronary vasoconstriction has been demonstrated during exercise. Human studies examining coronary artery dynamics during exercise are technically difficult to perform. Recently, noninvasive transthoracic Duplex ultrasound studies demonstrated that: 1) patients with left internal mammary artery (LIMA) grafts to the left anterior descending artery can be imaged; and 2) the LIMA blood flow patterns are similar to those seen in normal coronary arteries. Accordingly, subjects with LIMA to the left anterior descending artery were studied during handgrip protocols as blood flow velocity in the LIMA was determined. Beat-by-beat analysis of changes in diastolic coronary blood flow velocity (CBV) was performed in six male clinically stable volunteers (60 ± 2 yrs) during two handgrip protocols. Arterial blood pressure (BP) and heart rate (HR) were also measured and an index of coronary vascular resistance (CVR) was calculated as diastolic BP/CBV). Fatiguing handgrip performed at (40% of maximal voluntary contraction; MVC) followed by circulatory arrest did not evoke an increase in CVR (P = NS). In protocol 2, short bouts of handgrip (15 s) led to increases in CVR (18 ± 3% at 50% MVC and 20 ± 8% at 70% MVC). BP was also increased during handgrip. Our results reveal that in conscious humans, coronary vasoconstriction occurs within 15 s of onset of static handgrip at intensities at or greater than 50% MVC. These responses are likely to be due to sympathetic vasoconstriction of the coronary circulation.